Immigrant selection systems and immigrant health - Barry R. Chiswick; Yew Liang Lee; Paul W. Miller (Institute for the Study of Labor (IZA), 2006)
This paper is an analysis of the determinants of self-reported health status of immigrants, with a particular focus on type of visa used to gain admission. The concept of health capital and an immigrant selection and adjustment model are employed. The empirical analysis uses the three waves of the Longitudinal Survey of Immigrants to Australia (panel I). Immigrant health is greater for immigrants who are younger, more educated, male, more proficient in English, and living outside of an immigrant ethnic enclave. Immigrant health is poorest for refugees and best for independent (economic) migrants, and declines with duration in the destination. There is, therefore, evidence for favorable selectivity on the basis of health status among family and especially independent migrants, as well as a tendency toward regression to the mean with duration in the destination.
urn:nbn:de:101:1-20090626184
Keywords: 330; Migranten; Gesundheit; Australien